Islamic Insurtech Conceptual Framework: A Proposal - Azrul Azlan Iskandar Mirza; Nurul Aini Muhamed; Aimi Fadzirul Kamarubahrin (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2021)
Introduction: Insurtech refers to the use of technology innovations designed to squeeze cost and maximize efficiency from the current insurance industry model. Insurtech is a combination of the word’s “insurance” and “technology,” inspired by the term fintech i.e. financial technology. Whilst insurance company already move forward, Islamic Insurtech seems not a popular terminology. It may not have unique characteristic from stakeholder’s perspective and therefore it may only be embedded in insurtech definition. Purpose: This paper aims to explore the potential of having Islamic insurtech in the global market and analyze the opportunity to establish a conceptual framework for Islamic Insurtech. Methodology: This study uses qualitative approach based on in-depth analyzing on literature, report and website propose subject of the study. Findings: It is hoped that it will benefit the Islamic insurance or Takaful players to remain relevant in the global market. Paper Type: General Review